Impementasi Sistem Pengendalian Internal Pemerintah (SPIP) Oleh Badan Pengawas Keuangan dan Pembangunan (BPKP) dan Inspektorat di Provinsi Jawa Tengah Berdasarkan Perspektif: PP. No 60 Tehun 2008 Tentang Sistem Pengendalian Internal Pemerintah (SPIP) - Hagi Hutomo Mukti (Universitas Negeri Semarang, 2019)
The aim of this article is to examine the Implementation of Government Internal Control System (SPIP) by the Financial and Development Supervisory Agency (BPKP) and Inspectorate in Central Java Province Based on Perspective: PP.No 60 Tahun 2008. This research uses qualitative research approach methods with the type of juridical-sociological research. The results of this study are the implementation of SPIP in Central Java Province: leadership commitment has not been supported to implement SPIP in accordance with applicable regulations; Risk Assessment, documented mapping has not been carried out; Control Activities, the implementation of the review is still limited to the formality of fulfilling data requests from the SKPD. (2) there are still obstacles in the implementation of SPIP including the Standard Operating Procedure (SOP) which is not yet perfect, Oversight has not been effective, Recommendations are not followed up, Delays in Office Financial Reports, Weak Control, and Weak Communication, Lack of Commitment, Leadership Non-conducive, the next Weak Human Resources who become the absence of Regional Regulation or there is no law on the implementation of SPIP, Problem of Time Period. Conclusions from the results of the study are still lacking commitment from SKPD Leaders in Central Java Province even though the Governor of Central Java to apply SPIP in accordance with applicable provisions has not yet been documented mapping and monitoring. The implementation of the review is still limited to the formalities for fulfilling data without evaluation and monitoring of activities